1998
DOI: 10.1088/0953-2048/11/10/051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe on the crystal growth morphology of Bi-Sr-Ca-Cu-O

Abstract: The effect of Fe on the crystal growth of was studied by a floating zone method. The result shows that the planar solid-liquid growth interface breaks down into a cellular growth interface with increasing Fe substitution in the feed rods of . The size of the single crystals decreases with the increase in Fe substitution in the feed rods. When Fe substitution content y is 0.06 in a feed rod, the Bi-2212 single crystals in an as-grown bar are too small to be visible. The maximum thickness along the c-axis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Tel. : +90 422 3410010x3720; fax: +90 422 3410037. grain formation and intergrain properties of the Bi-based system were highly influenced by the partial substitution of Cu by 3d-elements [2][3][4][5][6]. The substitution of Ni and Fe for Cu site showed a monotonically decrease on T c with the increase on the substitution levels.…”
Section: Introductionmentioning
confidence: 98%
“…Tel. : +90 422 3410010x3720; fax: +90 422 3410037. grain formation and intergrain properties of the Bi-based system were highly influenced by the partial substitution of Cu by 3d-elements [2][3][4][5][6]. The substitution of Ni and Fe for Cu site showed a monotonically decrease on T c with the increase on the substitution levels.…”
Section: Introductionmentioning
confidence: 98%
“…Intergrain properties of the Bi-based HT c system were influenced by the partial substitution of Cu by 3d-elements, such as Ni, Co and Fe (Pop et al, 1996a(Pop et al, , 1996b(Pop et al, , 1997Pop, 1999;Gu et al, 1998). The T c value decreased significantly with the substitution of Ni and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…A replacement of some of the copper atoms with other types of atoms will therefore change the superconductivity of Bi-2212. Several publications [7][8][9] studying the substitution of Cu by 3D elements in Bi-2212 showed that T c decreases linearly with the increase in Cu-site substitution by Fe and Co, with a slope of 5 K for every percent of Cu-site substitution [7]. In order to reveal the effects of Cu-site substitution by trivalent Al on the superconductivity of Bi 2 Sr 2 Ca 1 Cu 2 O x , in this paper we study the effect of Al doping on the crystal growth behaviour and the superconductivity of Bi 2 Sr 2 Ca 1 Cu 2 O x .…”
Section: Introductionmentioning
confidence: 99%